Dose reduction of non-vitamin K antagonist oral anticoagulants in patients with atrial fibrillation: A Danish nationwide cohort study. Issue 178 (June 2019) - Xing, Lucas Yixi; Barcella, Carlo Alberto; Sindet-Pedersen, Caroline; Bonde, Anders Nissen; Gislason, Gunnar Hilmar; Olesen, Jonas Bjerring
Abstract: Introduction: To investigate the patterns of dose reduction of non-vitamin K antagonist oral anticoagulants (NOAC) in patients with atrial fibrillation (AF). Materials and methods: Using Danish nationwide registries, we identified all non-valvular AF patients initiated on standard-dose NOAC during 2011–2017 who were followed until dose reduction. The absolute risk of dose reduction was presented as cumulative incidence both overall and according to baseline characteristics. Moreover, to assess baseline comorbidities related to dose reduction, adjusted Cox regression models were used. In subgroup analysis, we investigated dose reduction following acute myocardial infarction and/or percutaneous coronary intervention (MI/PCI), chronic kidney disease (CKD), turned 80 years, intracranial hemorrhage, peripheral bleeding, ischemic stroke, cancer, bone fracture, and antiplatelet treatment start. Results: Of 24, 489 patients included, 12.2% experienced dose reduction during the study period. Dabigatran treatment, higher age at inclusion, high CHA2 DS2 -VASc score, and high HAS-BLED score were related to higher risk of dose reduction. Baseline ischemic heart disease (IHD), heart failure, cancer, CKD, chronic obstructive pulmonale disease (COPD), and hypertension were independent predictors of dose reduction. In subgroup analysis with six-month follow-up, MI/PCI, CKD, intracranial hemorrhage, peripheral bleeding, and antiplatelet treatment therapy were strongly associated with dose reduction. Conclusions: Dose reduction of NOACs was observed in 12.2% of AF patients during 2011–2017 and was associated with dabigatran treatment, advanced age at baseline, high CHA2 DS2 -VASc score, and high HAS-BLED score. Among comorbidities, IHD, heart failure, cancer, CKD, COPD, and hypertension predicted dose reduction independently. During six-month follow-up, MI/PCI showed the strongest association with dose reduction. Highlights: NOAC dose reduction was observed in one tenth of AF patients during 2011–2017. More comorbidities and dabigatran treatment were associated with dose reduction. Age ≥ 65 at baseline increased the risk of dose reduction by 2 times independently. Acute myocardial infarction showed the strongest association with dose reduction. Guidelines for NOAC dose adjustment are not completely followed by clinicians.